Khoekhoe Lexical Borrowing in Regionalised Afrikaans - Christie, Camilla Rose (Stellenbosch Papers in Linguistics Plus, 2022)
This brief paper aims to draw attention to the widespread and ongoing phenomenon of lexical borrowing from Khoekhoe-branch languages into regional Afrikaans. A case study of one Afrikaans plant name loaned from Khoekhoe-branch languages, karee (Searsia lancea, Searsia spp.), is used to demonstrate how post-shift phonological attrition can lead to lexical conflation, and hence to semantic extension. This paper strongly recommends that public-facing scientific organisations take greater care when providing linguistic information to lay communities, and also motivates increased study of the behaviour of click consonants in a post-shift context in order to develop a clearer understanding of Khoekhoe-branch language history.